Abusive supervision and employee reactions: The moderating roles of high-performing employees - Philip Mensah; Obianuju E. Okeke-Uzodike (SA Journal of Human Resource Management, 2025)
Orientation: Prior research has identified several moderators that can mitigate the effects of abusive supervision on employee outcomes; however, the role of high-performing employees (HPEs) has been virtually overlooked.